A Black Jurist in a Slave Society : Antonio Pereira Rebouças and the Trials of Brazilian Citizenship - Grinberg, Keila (Book collections on Project MUSE., 2019)
Keila Grinberg's compelling study of the 19th century jurist Antonio Pereira Rebouças (1798-1880) traces the life of an Afro-Brazilian intellectual who rose from a humble background to play a key - and conflicted - role as Brazilians struggled to define citizenship and understand racial politics. One of the most prominent specialists in civil law of his time, Rebouças explained why blacks fought stridently for their own inclusion in society but also complicitly embraced an ethic of silence on race more broadly. Grinberg argues that while this silence was crucial for defining spaces of social mobility and respectability regardless of race, it was also stifling, and played an important role in quelling political mobilization based on racial identity.